Gravimetric composition analysis of solid waste generated in Cotijuba Island in Belém – PA (Research, Society and Development, 2021)
Given the current background of solid waste management in Brazil, it is necessary, in addition to the diagnosis of generation, the composition of these wastes, so that the planning and formulation of strategies are more effective and in line with the precepts of the National Policy of Solid Waste (NPSW). Thus, this study aimed to characterize the solid waste generated  in the Island of Cotijuba, identify the recyclable waste that is sold, compare these wastes with  a national context, and evaluate the working conditions of recyclable collectors who work on the Island, through interviews , carried out in a direct and semi-structured way, as well as the quantification and characterization of waste, through gravimetric analysis, consisting of three steps: quartering, identification and weighing of waste categories. With the gravimetric composition data, it was found that the dynamics of disposal of the types of waste present on the island of Cotijuba follow the national trend, and only for the paper and cardboard category there was a notable difference. Being the   blend with organic waste, the factor that makes the recycling of waste unfeasible, which in turn, becomes waste. Thus, the importance of selective collection was realized as an alternative to solving part of the problem of proper disposal of urban solid waste (USW), as it enables better reuse of recyclable materials and organic matter for the local community. Added to this, environmental education actions for the local community, training of cooperative members, and a solid waste management policy adapted to the reality of the Island are necessary.